(untitled) (Journal of Economic Research & Business Administration, 2016)
The structure of household income by source – this is an important characteristic of the formation of household wealth, as it gives an idea what kind of income sources most significant for households. Changing the structure of incomes of the population may be one of the factors influenc ing the gain or, conversely, the weakening of population differentiation in income. Households at the present stage is one of the important subjects of economic activity, the outcome of which depends not only on the welfare of individual economic units, but the entire population of the country. It is known that cash income households are the sum of money received by household members in the form of wages, income from business activity, social benefits (pensions, stipends, allowances and other payments), inter est, dividends and other property income, other cash receipts.